A prática da participação na política educacional do município de Diadema-São Paulo: a influência dos referenciais freireanos - Paulino, Simone Fabrini (2009)
This research is part of a deeper research, carried through by the Paulo Freire Chair on PUC-SP, called: The Paulo Freire presence on Brazilian Education: education public systems analysis, since the 90th decade . With the objective of studying the participation ways and how s, observing the limits and possibilities of a political democratic education on Diadema-SP, which intends to follow a city school in which the participation is already a construction process, identifying and analyzing at school, the influence of Freire referential for this participative construction. The analysis is based on Paulo Freire experience as the Educational Secretary of São Paulo s City and on Freire categories: the praxis, conscientization and becoming more. Corroborating with participation studies, this research uses as a referential too Diaz Bordenave and Licínio Lima. It is also supported on Vitor Paro and Rubens Camargo for study of the participation limits and conditions. Using the Ethnographic Case Study methodology, in the field, the following topics are developed: observations, documental analysis and interviews which, added to the theoretician referential and data review, results on conflict and contradiction identification, which needs to be dialogue and problem topics in favor of the participative democracy construction, in a permanent learning dialectic movement